2007
DOI: 10.1007/s11664-007-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Size Effects in Miniaturized Lead-Free Solder Joints

Abstract: Future reliability and quality control of microelectronics will greatly depend on a detailed understanding of the complex mechanical and thermal properties of miniaturized lead-free solder joints. Therefore, the question of the occurrence of size effects or dimensionally induced constraints, which could change the mechanical properties of solder joints in small dimensions dramatically, has become the focus of investigation. In this study we investigated the influence of decreasing gap size on the tensile, shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 25 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…However, as can be seen from Sn-Zn binary diagram, the peak around 200.6°C is due to the second-phase formation in solder matrix, while the b-Sn primary phase melts at 214.6°C. Actually, these results completely agree with that reported by El-Daly et al [11,12], where the same effect …”
Section: Thermal Behaviorsupporting
confidence: 93%
See 1 more Smart Citation
“…However, as can be seen from Sn-Zn binary diagram, the peak around 200.6°C is due to the second-phase formation in solder matrix, while the b-Sn primary phase melts at 214.6°C. Actually, these results completely agree with that reported by El-Daly et al [11,12], where the same effect …”
Section: Thermal Behaviorsupporting
confidence: 93%
“…Such samples are usually manufactured from standard bar-solder, which is melted and solidified in a steel mold. In order to obtain relevant constitutive data for real interconnections, specimens had to be scaled down to a typical solder joint size if one considers the extremely small solder volumes in modern microelectronic industry [12,13]. Therefore, the design optimization of solder joints could be conducted with different geometries to investigate the tensile behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In previous related studies, characterization of constitutive alloy behavior is usually done through tensile tests using standard specimens. To obtain a relevant constitutive data for real interconnections, the specimens had to be scaled down to a typical solder joint size if one considers the extremely small solder volumes in modern microelectronic industry [11,12]. Therefore, the design optimization of solder joints could be conducted with different geometries to investigate the tensile behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the ball shear tests, lap-shear tests can exert a similar stress concentration occurring close to the attachment interface at both ends of the joints and reflect the mechanical behavior of BGA solder joint more accurately. By using lap-shear tests, Chawla et al [9][10][11][12][13] found that the testing and geometrical parameters have profound effects on the mechanical behavior and fracture location of rectangular solder joints.…”
Section: Introductionmentioning
confidence: 99%